Determinants of heterosexual men's demand for long-acting injectable pre-exposure prophylaxis (PrEP) for HIV in urban South Africa - Chih-Yuan Cheng; Matthew Quaife; Robyn Eakle; Maria A. Cabrera Escobar; Peter Vickerman; Fern Terris-Prestholt (BMC Public Health, 2019)
Abstract Background Heterosexual men in South Africa are a large key population to exposure to HIV, yet preferences for HIV pre-exposure prophylaxis (PrEP) among this population have not, to date, been investigated in the literature. This paper aims to explore HIV prevention preferences among heterosexual men in urban South Africa, as well as to examine the demand and characteristics of men who favour long-acting injectable (LAI) PrEP over condoms and oral PrEP. Methods Data were collected among 178 self-reported HIV-negative heterosexual men, who were given example products and information before being asked which they preferred. Multivariate logistic regression was used to analyse which characteristics were associated with product choice. Results 48% (n = 85) of participants preferred LAI PrEP, while 33% (n = 58) and 20% (n = 35) chose oral PrEP and condoms respectively. Having children (marginal effect = 0.22; 95% CI [0.01, 0.44]) or having higher risk attitude scores (marginal effect = 0.03; 95% CI [0.01, 0.06]) was significantly associated with a choice of LAI PrEP, while those who had unprotected anal intercourse (marginal effect = − 0.42; 95% CI [− 0.57, − 0.27]) and those who were concerned with protection against other sexually transmitted infections over HIV (marginal effect = − 0.42; 95% CI [− 0.60, − 0.24]) appeared less likely to prefer LAI PrEP. Conclusions The results suggested a relatively high demand and theoretical acceptability for LAI PrEP among heterosexual men in urban South Africa, but there appeared to be fewer distinct predictors for the willingness to use LAI PrEP compared to studies conducted among gay and bisexual men and women. Nevertheless, the findings contribute to the mapping of the demand and determinants of heterosexual men’s preferences for novel antiretroviral-based prevention in sub-Saharan Africa, and the data could aid in the differentiated design of future HIV prevention strategies using LAI PrEP in conjunction with other methods.